2017
DOI: 10.1016/j.autrev.2017.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Bone mineral density and vitamin D status in systemic lupus erythematosus (SLE): A systematic review

Abstract: Despite the improvement in the quality of life of patients with SLE due to scientific and technological advances, SLE remains a disease that over the years may produce irreversible damage to patients. Osteoporosis and secondary bone fractures are two of the major causes of irreparable injury in patients with SLE. Vitamin D insufficiency may play a vital role both in reduced bone mineral density (BMD) and in the appearance of fractures, although its mechanisms of action are still unclear. We performed a systema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
33
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 61 publications
2
33
0
Order By: Relevance
“…For patients receiving GC, the recent guidelines of the American College of Rheumatology for the prevention and treatment of GC-induced osteoporosis should be followed. 3 We fully agree with Orsolini et al that a future update of the EULAR recommendations for the management of SLE should include specific guidance regarding bone health.…”
supporting
confidence: 78%
“…For patients receiving GC, the recent guidelines of the American College of Rheumatology for the prevention and treatment of GC-induced osteoporosis should be followed. 3 We fully agree with Orsolini et al that a future update of the EULAR recommendations for the management of SLE should include specific guidance regarding bone health.…”
supporting
confidence: 78%
“…There is a multifactorial etiology of bone loss in SLE, which includes systemic inflammation; serological, metabolic, and hormonal factors; and maybe also genetic factors and medication (5)(6)(7)(8). Moreover, a high prevalence of morphometric vertebral fractures was observed in SLE patients, although 1/3 had normal bone density, in line with the multifactorial etiology of fractures in SLE (3)(4)(5).…”
Section: Introductionmentioning
confidence: 83%
“…Systemic lupus erythematosus (SLE) is one of the most complex multisystemic autoimmune diseases as it encompasses a wide spectrum of clinical and serological manifestations ( 1 , 2 ). Recent studies demonstrate a higher incidence of osteoporosis (OP) and fractures in SLE patients than in healthy subjects (HS) ( 3 5 ). There is a multifactorial etiology of bone loss in SLE, which includes systemic inflammation; serological, metabolic, and hormonal factors; and maybe also genetic factors and medication ( 5 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…Systemic inflammation, glucocorticoid use, lupus nephritis, premature menopause and vitamin D deficiency all have deleterious effects on bone health. Numerous studies have demonstrated that lower vitamin D levels are associated with higher SLE disease activity, although trials of vitamin D supplementation for reducing SLE disease activity have had conflicting results 4–7. Data on vitamin D supplementation for bone health in SLE are mostly derived from observational studies, raising concerns about confounding by indication; patients with SLE perceived to be at highest risk for fracture may be more likely to receive vitamin D.…”
Section: Introductionmentioning
confidence: 99%